Lifespan Analysis of Dystrophic mdx Fast-Twitch Muscle Morphology and Its Impact on Contractile Function - Kiriaev, Leonit; Kueh, Sindy; Morley, John W.; North, Kathryn N.; Houweling, Peter J.; Head, Stewart I. (Frontiers in Physiology, 2021)
Duchenne muscular dystrophy is caused by the absence of the protein dystrophin from skeletal muscle and is characterized by progressive cycles of necrosis/regeneration. Using the dystrophin deficient mdx mouse model we studied the morphological and contractile chronology of dystrophic skeletal muscle pathology in fast-twitch EDL muscles from animals 4-22 months of age containing 100% regenerated muscle fibers. Catastrophically, the older age groups lost ~80% of their maximum force after one eccentric contraction of 20% strain, with the greatest loss ~93% recorded in senescent 22 month old mdx mice. In old age groups there was minimal force recovery ~24% after 120 minutes, correlated with a dramatic increase in the number and complexity of branched fibers. This data supports our two-phase model where a “tipping point” is reached when branched fibers rupture irrevocably on eccentric contraction. These findings have important implications for pre-clinical drug studies and genetic rescue strategies.